The leadership academy: a new approach for changing times in communication sciences and disorders programs. - Scudder R; Self T; Cohen PA (Perspectives on Issues in Higher Education, 2010)
Challenges facing academic programs in Communication Sciences and Disorders include dwindling resources and increased pressure to maintain faculty members and grow program enrollments. This article presents a model of a leadership academy established in a College of Health Professions for faculty and staff. The academy emphasizes an adaptive approach designed to change the culture of the academy and to provide a changing view of leadership as an activity, not a position of authority. A Fellow of the academy describes her experiences and changing views of leadership.